P616 Sustainability of thiopurines monotherapy in ulcerative colitis: a nationwide analysis from the epi-IIRN cohort. (27th May 2021) - Atia, O; Friss, C; Mendelovici, A; Shteyer, E; Orlanski-Meyer, E; Ledderman, N; Greenfeld, S; Kariv, R; Loewenberg Weisband, Y; Gabay, H; Nevo, D; Matz, E; et al.
Abstract: Background: Thiopurines have been long used to maintain remission in ulcerative colitis (UC) but are also associated with toxicity and therapeutic failure. We aimed to assess the sustainability rate of thiopurines commenced as monotherapy in UC, and to explore predictors of sustainability. Methods: This study was performed on data from four Health Maintenance Organizations (HMOs), covering 98% of the Israeli population. We included all biologic-naïve UC patients diagnosed after 2005 and treated with thiopurines monotherapy for at least three months. Treatment with 5- aminosalicylic acid (ASA) was allowed if initiated prior to or during the first three months from initiation of thiopurines. Sustainability was defined as continued thiopurines treatment without switching therapy, adding biologics or requiring surgery. At most one short steroid course was allowed. Cox regression model was used to explore estimated predictors to sustainability. Results: A total of 1, 897 (370 [20%] pediatric-onset and 1, 527 [80%] adults) thiopurines-treated patients were included with a 15, 033 person-years of follow-up. The median time from UC diagnosis to initiation of thiopurines was 12.7 months (IQR 4.6–30.9), and the median treatment duration was 13.0 months (6.3–28.4). Sustainability rate was evident in 92% of patients after 6 months from initiation of thiopurines and 83%, 65% and 42% at one, three and five years, thereafter. Sustainability was associated with early initiation of thiopurines during disease course (HR 0.99 [95%CI 0.985–0.995]) and lack of 5-ASA at initiation of thiopurines (HR 0.7 [95%CI 0.6–0.8]). Conclusion: As many as two thirds of biologic-naïve UC patients treated with thiopurines monotherapy sustain this treatment after five years, especially when initiated early and without 5-ASA.